Synthesis of New Chiral and Nonchiral Pyrido [3,2-e],[1,3,4] oxadiazine Derivatives - L. S. Shet; A. R. Shelar; F. V. Manvi (E-Journal of Chemistry)
A chiral series of 6,7-dichloro-3-[3-(2,2-dihalovinyl)-2,2-dimethylcyclopropyl] -1H-pyrido [3,2-e],[1,3,4] oxadiazines (a-f) and a nonchiral series of 3-substituted, 6,7-dichloro-1H-pyrido [3,2-e][1,3,4] oxadiazines (a-g) have been synthesized. The synthesized compounds were characterized by IR, 1H NR, HPLC and mass spectral data.